(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Tereshuk A. I. Рroblems professionally orientation and self high school students. The problems of professional orientation of students and professional self seniors, analyzes the features of the traditional system of vocational guidance in the search for new ways of solving problems.